Yahudi ahit geleneğinde Nuh kanunları ve Nuhilik - Hasanov, Eldar (My University, 2012)
YAHUDİ AHİT GELENEĞİNDE NUH KANUNLARI VE NUHİLİK Yahudiliğe göre Sina vahyinden önce verilen kurallar manzumesi Nuh Kanunları olarak adlandırılır. Yahudilik, Tanrı-insan iletişiminin ilk insanla başladığını kabul etmektedir. Bu iletişim ahitleşme olarak ifade edilmektedir. Ahitleşme sırasında birtakım hükümler konulur. İlk insan Âdem’e hükümler verilmiş, sonradan Nuh’la ahitleşmede bu hükümler tekrarlanmış ve sayısı çoğaltılmıştır. Bu hükümler Yahudi ilahiyatında Nuh Kanunları adıyla bilinmektedir. Nuh Kanunları’nın içeriğine dair erken dönem Yahudi kaynaklarında ittifak olmayıp farklı sayılar ve farklı hükümlerden bahsedilmiştir. İçeriğin son haline gelmesi Ortaçağ’da gerçekleşmiştir. Bu nedenle günümüz bazı Yahudi entelektüeller Nuh Kanunları’nın rabbinik dönem öncesi Yahudilikte mevcut olmayıp sonradan sosyal ve siyasal ihtiyaçlara binaen rabbiler tarafından tesis edildiği iddialarını dile getirmişlerdir. Yahudi ilahiyatında donatıldığı işlevler bakımından Nuh Kanunları önemli bir konuma sahiptir. Sina öncesi döneme ait olması bakımından bu kavram hukuk düşüncesinin gelişimine örnek gösterilmiştir. İçeriğinin oldukça genel olup tabii düzenin korunmasını hedeflemesi bakımından, Yahudilikte Tabii Hukuk düşüncesinin varlığına örnek gösterilmiştir. Ayrıca hitap alanının sınırsızlığı bakımından da Evrenselcilik kuramının Yahudilikteki ifadesi olarak görülmüştür. Son olarak, Nuh Kanunları kimlik bağlamında da çok önemli konuma sahiptir. Yahudi olmayanlara bakış konusunda bu kavram temel ölçüt olup pratikte Nuhi kimliğini doğurmuştur. Günümüz Yahudi kaynaklarında yer alan bilgilere göre Yahudi olmayanlar Mesih döneminde Nuhi kimliğinde olacaklardır. Sosyal bir hareket olarak Nuhilik 20. yüzyılın son çeyreğinde ortaya çıkmıştır ve Mesih dönemine zemin hazırladığı düşünülmektedir.

NOAHIDE LAWS IN JEWISH COVENANT TRADITION AND NOAHISM The term of Noahide Laws is a general term for the rules given in pre-Sinai period. According to Judaism, God-human communication starts with the first humankind. Such communication expressed terminologically as covenant. The covenantal procedure introduces certain provisions. In the beginning, the first man, Adam, was commanded with provisions. God made covenant with Noah and as the content of this covenant, the provisions given to Adam were re-introduced to Noah too with one additional rule. The provisions given to Noah are referred in Judaism with the concept of Noahide Laws, or, with the full translation, The Seven Commandments of the Sons of Noah. There is no consensus in early Jewish sources on the content of the Noahide Laws. There are different views mentioned for both the number and the very provision of Noahide Laws. This disagreement continued till the end of Middle Age. Because of this fact, there are some views by contemporary Jewish scholars which claim that the concept of Noahide Laws took no place in the pre-rabbinic times and had been fabricated later, due to social and political needs. The concept of Noahide Laws is significant with regard of the functions equipped in Jewish theology. On account of its affiliation to the pre-Sinai period legal thought, this concept is seen as example of the development of notion of law and legal thinking. With regard of its being totally general and targeting the protection of the natural order, this concept is held up as a sample which demonstrates existance of the idea of Natural Law in Jewsih tradition. Furthermore, with regard of its being unlimitedness in addressing, this concept is held up as the expression of the theory of Universalism. Finally, the concept of Noahide Laws has significant position in the context of identity issues. This concept is considered the main criterion in the view to non-Jews. In parallel to this criterion, Jewish theology conceptualized Noahide identity, or, with the full translation, Noah’s son/ daughter. According to contemporary Jewish sources, all non-Jews will take this identity in the Messianic period. As a social movement, Noahism emerged in the last quarter of the 20th century. According to contemporary Jewish sources, it is considered as more the movement grows as better it prepares the way to the Messianic period.
Keywords: Din; Nuhilik; Yahudilik